Document repairs - Wardle, David Bernard (London : Society of Archivists, 1971)
The handbook aims to be a practical guide to document repair work, useful to both archivists and craftsmen.
Includes index.
aia 19/06/2017
Loans
Keywords: Conservation of manuscripts; Archives